Massive necrotizing fasciitis: a life threatening entity. Issue 11 (5th November 2019) - Vilallonga, Ramon; Mazarro, Alejandro; Rodríguez-Luna, María Rita; Caubet, Enric; Fort, José Manuel; Armengol, Manuel; Guirao, Xavier
Abstract: Necrotizing fasciitis (NF) is a complicated soft tissue infection frequently associated with severe sepsis if an early medical and surgical treatment is not performed. We report two postoperative cases of severe NF after oophorectomy and colorectal resection. Because of the similarity with more benign skin infections at the early steps, clinical suspicion is crucial. Surgical exploration and resection will provide both the diagnosis confirming necrotizing infection of the fascia with vessels and treatment. Also, empirical broad-spectrum antibiotics must be initiated as soon as possible. Regardless of the presence of risk factors, NF is a condition with a high mortality rate and only an expeditious and undelayed treatment may improve the patient's outcome. Surgical focus control requires wide and repeated resections, and planned reconstructive plastic surgery might be necessary.